2001
DOI: 10.1034/j.1600-0765.2001.360202.x
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic comparison of periodontal ligament cells in vivo and in vitro

Abstract: The mammalian periodontal ligament contains heterogeneous populations of connective tissue cells, the precise function of which is poorly understood. Despite close proximity to bone and the application of high amplitude physical forces, cells in the periodontal ligament (PL) are capable of expressing regulatory factors that maintain PL width during adult life. The study of PL homeostasis and PL cell differentiation requires culture and phenotypic methods for precise characterization of PL cell populations, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
98
0
6

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(107 citation statements)
references
References 29 publications
(47 reference statements)
1
98
0
6
Order By: Relevance
“…A total number of 12 clones, namely PC1-PC12, were cloned from primary PDL-derived cells, which are believed to comprise progenitor cells of PDL-producing fibroblasts, of cementoblats (cells that form cementum, a mineralized matrix layer covering the tooth root) and of bone forming osteoblasts (Ivanovski et al 2006, Kramer et al 2004, Lekic et al 2001, McCulloch and Bordin 1991, Melcher 1976, Seo et al 2004. Although all 12 clones had an ability to form CFU-F, only PDL clones PC2, PC3, PC4, PC8 and PC12 underwent adipogenic and osteoblastic differentiation, suggesting stem cell-like characteristics of these clones.…”
Section: Discussionmentioning
confidence: 99%
“…A total number of 12 clones, namely PC1-PC12, were cloned from primary PDL-derived cells, which are believed to comprise progenitor cells of PDL-producing fibroblasts, of cementoblats (cells that form cementum, a mineralized matrix layer covering the tooth root) and of bone forming osteoblasts (Ivanovski et al 2006, Kramer et al 2004, Lekic et al 2001, McCulloch and Bordin 1991, Melcher 1976, Seo et al 2004. Although all 12 clones had an ability to form CFU-F, only PDL clones PC2, PC3, PC4, PC8 and PC12 underwent adipogenic and osteoblastic differentiation, suggesting stem cell-like characteristics of these clones.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that human PDL contains a heterogeneous population of cells (Lekic et al 2001;Murakami et al 2003) capable of differentiating into cementoblasts or osteoblasts in vitro. Recently, Seo et al (2004) proved that human periodontal ligament cells contained stem cells (periodontal ligament stem cells, PDLSCs) and the application of these stem cells is a promising therapeutic approach for reconstruction of tissues destroyed by periodontal diseases.…”
mentioning
confidence: 99%
“…It is responsible for anchoring and supporting the tooth within the tooth socket. The periodontal ligament is composed of a heterogeneous population of cells containing fibroblasts, osteoblasts and cementoblasts (Bartold et al, 2000;Gay et al, 2007;Lekic et al, 2001;Seo et al, 2004;Shimono et al, 2003). Early studies have suggested that the PDL tissue had regenerative or repair abilities when an injury was incurred by the periodontal tissue (Reviewed in Bartold et al (2005) and Shimono et al (2003)).…”
Section: Periodontal Ligament Stem Cellsmentioning
confidence: 99%